Prevalence and predictors of food insecurity among people living with HIV affiliated with AIDS service organizations in Ontario, Canada. Issue 5 (4th May 2018) - Bekele, Tsegaye; Globerman, Jason; Watson, James; Jose-Boebridge, Murray; Kennedy, Richard; Hambly, Keith; Anema, Aranka; Hogg, Robert S.; Rourke, Sean B.; ,
ABSTRACT: Up to half of people living with HIV in resource-rich settings experience moderate to severe food insecurity. Food insecurity, in turn, has been linked to adverse health outcomes including poor antiretroviral adherence, poor HIV viral suppression, frailty, and mortality. We estimated the prevalence of food insecurity among 649 adults living with HIV and recruited from community-based AIDS service organizations in Ontario, Canada. Food security was assessed using the Canadian Household Food Security module. We used logistic regression modeling to identify demographic, socioeconomic, and psychosocial factors independently associated with food insecurity. Almost three-fourths of participants (70.3%) were food insecure and a third (31%) reported experiencing hunger. The prevalence of food insecurity in this sample is approximately six times higher than that of the general population. Factors independently associated with food insecurity were: having dependent children at home, residing in large urban areas, low annual household income (<$40, 000), difficulty meeting housing-related expenses, cigarette smoking, harmful drug use, and depression. Broad, multisector interventions that address income, housing affordability, substance use and mental health issues are needed and could offset future public health expenditures.